Corporate Criminal Liability in Environmental Cases - Fernando, Youngky (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
Rapid industrial growth often has a negative impact on the environment. Not infrequently, various cases of environmental pollution and destruction are carried out by corporations that prioritize profit without considering sustainability aspects. Therefore, the application of criminal liability to corporations is crucial in efforts to enforce environmental law. This study aims to analyze the concept and application of criminal liability for corporations in environmental cases in Indonesia. The research method used is a normative legal approach with an analysis of laws and regulations, court decisions, and related case studies. The results of the study indicate that although the Environmental Protection and Management Law has regulated the mechanism for corporate criminalization, its implementation still faces various obstacles, such as proving corporate guilt and identifying responsible managers. In addition, the criminal sanctions imposed tend to be more administrative and financial in nature, while the environmental recovery aspect is not yet fully optimal. This study recommends the need to strengthen legal instruments and the capacity of law enforcement officers to ensure corporate accountability and sustainable environmental protection.